Upaya Meningkatkan Kualitas Kuliah Teknik Komputasi melalui Pembelajaran Berbasis Contextual Teaching Learning - Ariade Chandra Nugraha; Deny Budi Hertanto (Faculty of Engineering, Universitas Negeri Yogyakarta, 2014)
This study investigates the effect of Contextual Teaching Learning (CTL) on the students’ motivation, understanding, and final assessment in the course of Computational Engineering. CTL allows students to participate and play an active role in learning to improve achievements. This study was a classroom action research. The subjects of this study were the students of the Study Program of Mechatronics, Faculty of Engineering, Yogyakarta State University who took the course of Computational Engineering. The data collection was conducted using observation, closed questionnaires, interviews and open questionnaires. The results showed CTL could increase the students’ motivation indicated by the increasing number of students who asked questions during the lectures from 5% to 60%. In addition, the students' understanding of the materials was also increased evidenced by the ability of the students to complete the task without the lecturers’ assistance from 25% to 100% at the end of the third cycle. At the end of the third cycle, 80% of the member of the students had reached more than the score of B, and it is expected by the end of the semester, all students would get more than the score of B.